2009
DOI: 10.1179/135100009x12525712409850
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cycle exercise on acetone in expired air and skin gas

Abstract: This study investigated the influence of cycle exercise on acetone concentration in expired air and skin gas. The subjects for this experiment were eight healthy males. Subjects performed a continuous graded exercise test on a cycle ergometer. The workloads were 360 (1.0 kg), 720 (2.0 kg), 990 (2.75 kg) kgm/min, and each stage was 5 min in duration. A pedaling frequency of 60 rpm was maintained. Acetone concentration was analyzed by gas chromatography. The acetone concentration in expired air and skin gas duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…While not as powerful as caloric restriction, exercise affects breath acetone near the time of exercise and over the course of days. During exercise, breath acetone can increase by approximately 1 ppm depending on the initial state of ketosis, intensity, and duration . In the hours following exercise, breath acetone is expected to increase based on the behavior of BOHB ; however, confirmatory studies are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While not as powerful as caloric restriction, exercise affects breath acetone near the time of exercise and over the course of days. During exercise, breath acetone can increase by approximately 1 ppm depending on the initial state of ketosis, intensity, and duration . In the hours following exercise, breath acetone is expected to increase based on the behavior of BOHB ; however, confirmatory studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In some subjects, BrAce fell at the onset of exercise and then increased with continued exercise . During graded exercise tests, BrAce increased (∼twofold) with exercise intensity , maximum BrAce corresponded to the onset of the lactate threshold , and the fat oxidation rate was shown to be logarithmically related to BrAce . Additionally, the fat oxidation rate and BrAce were shown to have parallel increases over 2 h of steady treadmill exercise .…”
Section: Factors Affecting Bracementioning
confidence: 93%
See 1 more Smart Citation
“…Sasaki et al (2011) reported that acetone concentration in expired air increased during graded and prolonged exercise such as walking or running. We have reported that acetone concentrations emanated from skin gas and in expired air increased with high exercise intensities of cycle exercise (Yamai et al 2009) and hand-grip exercise (Mori et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Acetone, along with other ketones, like 3-hydroxybutrate and acetoacetate are generated within the liver and are formed by the oxidation of fatty acids and used as fuel for peripheral tissues during times of starvation, exercise, in obese people or when insulin levels are extremely low as are seen in diabetic patients [7,8].…”
mentioning
confidence: 99%